Strategic Price Response in the Differentiated U.S. Yogurt Market - Mohammed, Rezgar; Murova, Olga (International Journal of Economics and Financial Issues, 2019)
Pricing decision is the most important decision made by food manufacturers. Although products are offered at regular prices most of the time, they are periodically offered at discounted prices to boost sales. In a differentiated product market, how brands respond to each other’s price change is not addressed very often empirically. This paper studies a strategic price response to perceive how brands response to each other’s prices in the U.S. differentiated yogurt market. This paper also estimates the frequency of price promotion to answer the question of whether private labels go on price promotion less or more frequently than main national brands. Vector autoregressive estimates suggest that the price pattern of yogurt brands is systematic and there is a strategic decision in setting prices. Granger-causality test shows that both Yoplait and private labels alter prices of other brands by having a significant impact on their pricing decision. Results of the impulse response functions confirm that Yoplait with the highest market share is the price leader in the yogurt market where all brands respond significantly to Yoplait’s price shock up to five weeks following an impulse. The Markov-switching regression shows that private labels go on price promotion as frequently as national brands. Keywords: yogurt; strategic price; Granger-causality; impulse response; Markov-switching JEL Classifications: C32, C33, D22, L11 DOI: https://doi.org/10.32479/ijefi.8708